TRACKING THE ROOTS OF RADICALISM IN INDONESIA: INTERPRETATION OF THE VERSIONS OF JIHAD AND WAR IN THE QUR’AN - Zulfa, Wildana (Universitas Nurul Jadid, 2022)
Wars and fundamental actions in Indonesia, such as terrorism, seem to be a stigma attached to Islam. If you look at previous history, this stigma appeared for the first time when the WTC incident on September 11, 2011, in the United States, was followed by the bombings in Bali (2002), Madrid (2004), London (2005), and in Paris (2015). carried out by the radical Islamic movement, al-Qaida. This is where the world community is haunted by the discourse of Islamophobia and attaches various negative stigmas to Islam, such as radical Islam, fundamental Islam, extreme Islam, militant Islam, terrorist Islam, and so on. This research will focus on the problems above, with the formulation of the problem; How is the interpretation of the verse of jihad and war, and how is it related to the Qur’an?